The impact of a maternal mental health intervention on intimate partner violence in Northern Ghana and the mediating roles of social support and couple communication: secondary analysis of a cluster randomized controlled trial - Jiepin Cao; John A. Gallis; Mohammed Ali; Margaret Lillie; Safiyatu Abubakr-Bibilazu; Haliq Adam; Elena McEwan; John Koku Awoonor-Williams; John Hembling; Joy Noel Baumgartner (BMC, 2021)
Abstract Backgrounds Diverse intervention efforts are implemented to address intimate partner violence (IPV) against women. Via a syndemics theory lens and emerging empirical evidence, mental health interventions demonstrate promise to partially ameliorate IPV. However, the mechanisms of change underlying many IPV interventions are not well understood. These gaps impede our efforts to strengthen or integrate effective components into the current mental health resources, especially in low- and middle-income countries (LMICs). This study aims to examine the impact of a maternal mental health intervention called Integrated Mothers and Babies Course & Early Childhood Development (iMBC/ECD) on IPV and whether social support and/or couple communication mediates the intervention effects among women in rural, Northern Ghana. Methods The current study is a secondary data analysis of a cluster randomized controlled trial. IPV was measured at baseline and 8 months post-intervention (~ 19 months post-baseline). At baseline, 84.8% of the women enrolled in the study (n = 374) reported some type of IPV in the past 12 months. Logistic regression models and multiple mediation analyses were used to address the study aims. Results iMBC/ECD did not reduce IPV in the intervention group compared to the control group. Social support and couple communication did not mediate the intervention effects on IPV as indicated by the indirect effects of the multiple mediation models. However, increase in social support reduced women's odds of experiencing emotional violence by 7%, odds ratio (OR) = 0.93, p = 0.007; b = − 0.07, 95% confidence interval (CI) = (− 0.13, − 0.02), and improvement in couple communication demonstrated promise in reducing women's odds of experiencing controlling behaviors by 7%, OR = 0.93, p = 0.07; b = − 0.07, CI = (− 0.14, 0.005), though the improvements were not due to the intervention. Conclusion This maternal mental health intervention did not reduce IPV; however, the findings extend our knowledge about the impact of such interventions on IPV and the potential mechanisms of change via social support and couple communication. Future research evaluating the impact of mental health interventions on IPV and mechanisms of change is essential for the development of effective interventions. Future programs addressing IPV in LMICs should consider risk factors beyond relationship level (e.g. poverty and gender inequity). Trial registration ClinicalTrials.gov # NCT03665246 , Registered on August 20th, 2018.